EVALUATING THE PERFORMANCE OF BANKS AND THEIR ROLE IN PROMOTING SUSTAINABLE DEVELOPMENT (World Economics and Finance Bulletin, 2022)
This study aims to determine the impact of using the performance appraisal approach for banks in promoting sustainable development, as this helps support investors’ decisions to invest in these companies. The process of evaluating the performance of banks is of paramount importance that aims to achieve the best use of resources to reach the highest return with the lowest risk and the lowest possible cost, since the traditional systems used in evaluating banking performance are deficient and meet the requirements of performance evaluation and evaluation in contemporary banks, so it is necessary to resort to Banks evaluation methods are more useful. And the search reached Banks’ lack of an internal audit division, which may lead to some errors and not being avoided during work, lack of staff in the investment department compared to the total owners of the banks subject to evaluation, which may lead to a lack of flow and ease of work in the aforementioned department, low percentage of investment department employees participating in courses Developmental.